Types of violence and sociodemographic factors associated with intragender violence in Colombia - Redondo Pacheco, Jesús (2023)
At present, there are few studies on violence carried out between same-sex couples or in which one of the members is transsexual, transgender or intersexed, it will present invisibility and difficulty in its detection. The objective of this article was to identify the types of violence and sociodemographic factors associated with violence between same-sex couples in Barrancabermeja, Bucaramanga and its metropolitan area (Colombia). A total of 152 subjects belonging to the LGBTIQ community aged between 18 and 60 years old (M = 26.0; SD = 29.6) participated. The participants responded to two online instruments: the Sociodemographic File and the Partner Abuse Experiences Checklist (Form A). Our results indicate different types of intimate partner violence (psychological, followed by emotional, physical, economic, and finally sexual violence) associated with sociodemographic factors such as sexual orientation, gender, educational level, and occupation. Intervention and prevention programs must be designed to address and reduce this type of violence, which is also prevalent in sexual minorities.